Prevalence and Distribution of Rotavirus Genotypes Among Children With Acute Gastroenteritis in Areas Other Than Java Island, Indonesia, 2016–2018 - Wahyuni, Rury Mega; Utsumi, Takako; Dinana, Zayyin; Yamani, Laura Navika; Juniastuti,; Wuwuti, Ishak Samuel; Fitriana, Elsa; Gunawan, Emily; Liang, Yujiao; Ramadhan, Fitratul; Soetjipto,; Lusida, Maria Inge; et al. (Frontiers in Microbiology, 2021)
Group A rotaviruses (RVAs) are the leading cause of acute gastroenteritis, which is often associated with severe symptoms in children under five years old. Genetic reassortments and interspecies transmission commonly occur, resulting in a great diversity of RVA circulating in the world. The aim of this study is to determine the prevalence and distribution of RVA genotypes among children in Indonesia over the years 2016–2018 across representative areas of the country. Stool samples were collected from 202 pediatric patients with acute gastroenteritis in three regions of Indonesia (West Nusa Tenggara, South Sumatra and West Papua) in 2016–2018. Rotavirus G and P genotypes were determined by reverse transcription polymerase chain reaction (RT-PCR) and direct sequencing analysis. The prevalences of RVA in South Sumatra (55.4%) and West Papua (54.0%) were significantly higher than that in East Java (31.7%) as determined in our previous study. The prevalence in West Nusa Tenggara (42.6%) was the lowest among three regions, but higher than that in East Java. Interestingly, equine-like G3 rotavirus strains were found as predominant strains in South Sumatra in 2016 and in West Papua in 2017–2018. Moreover, the equine-like G3 strains in South Sumatra detected in 2016 were completely replaced by human G1 and G2 in 2018. In conclusion, RVA infection in South Sumatra and West Papua was highly endemic. Equine-like G3 strains were also spread to South Sumatra (West Indonesia) and West Papua (East Indonesia) as well as Java Island. Dynamic change in Rotavirus genotypes from equine-like G3 to human genotypes was also observed. Continuous monitoring may be warranted in isolated areas in Indonesia.